Taxonomic status of Harlan’s Hawk Buteo jamaicensis harlani (Aves: Accipitriformes) - Clark, William S. (Zootaxa, 2018)
Since its description in 1830 by Audubon, Harlan’s Hawk (taxon harlani) has been considered both as a species (Buteo harlani) (1830–1891 and 1944–1972) and as a subspecies of Red-tailed Hawk (B. jamaicensis harlani) (1891–1944 and 1973 to present). Both decisions making it a subspecies lacked sufficient taxonomic justification, whereas the 1944 decision to consider it a species was supported by convincing arguments. I conducted field and museum work over many years to better understand the morphology and taxonomic status of harlani and how this taxon differs from other taxa currently included in B. jamaicensis. Some hybridization between these taxa has been reported, as has been between many other species of Buteo. The taxon harlani is distinguished from all subspecies of B. jamaicensis in plumage, including the extent of feathering on the tarsus. The species occupies a breeding range parapatric, but with some overlap, to that of B. jamaicensis but occasionally breeds within a large area of the range of the latter in western Canada. It should be considered a full species based on lack of justification for considering it a subspecies, and the many differences between it and B. jamaicensis, which are greater than differences between any two subspecies of diurnal raptor.